2018
DOI: 10.1038/s41598-018-32689-4
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of multi-day learning and savings in sensorimotor adaptation

Abstract: In the present study we evaluated changes in neural activation that occur over the time course of multiple days of sensorimotor adaptation, and identified individual neural predictors of adaptation and savings magnitude. We collected functional MRI data while participants performed a manual adaptation task during four separate test sessions over a three-month period. This allowed us to examine changes in activation and associations with adaptation and savings at subsequent sessions. Participants exhibited reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 50 publications
(102 reference statements)
3
29
0
Order By: Relevance
“…It is likely that there is an insufficient error stimulus in the early or late phases for the effects of ctDCS to be observable 49 . This is also supported by neurophysiological studies which report that activation of the cerebellum depends on the time scale of adaptation 50 where cerebellar activation decreases over time 5 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It is likely that there is an insufficient error stimulus in the early or late phases for the effects of ctDCS to be observable 49 . This is also supported by neurophysiological studies which report that activation of the cerebellum depends on the time scale of adaptation 50 where cerebellar activation decreases over time 5 .…”
Section: Discussionsupporting
confidence: 53%
“…A recent fMRI study identified neural predictors of adaptability by evaluating the time course of activation over four sessions of a visuomotor adaptation task. Faster adaptation in later sessions was associated with activation of non-cerebellar regions, while slower adaptation was associated with greater activation in the M1-cerebellar motor loop 50 . Therefore, increasing the excitability of the cerebellum with anodal ctDCS may cause slower adaptation as reflected by the cumulative and consecutive-session estimates in this study.…”
Section: Discussionmentioning
confidence: 89%
“…Likewise, Wolpe et al 46 found that decreased sensorimotor adaptation with aging was associated with reduced gray matter volume in regions linked to explicit learning (e.g., the striatum and prefrontal cortex) and not the cerebellum. Finally, a recent study found that activation in brain regions related to cognitive processes, including striatal, parietal, and cingulate cortical areas positively correlated with sensorimotor savings 63 . Interestingly, the striatum is thought to function as an adaptive search mechanism that retrieves the appropriate sensorimotor representations for a given environment 64 .…”
Section: The Effects Of Aging On Visuomotor Adaptation and Retention mentioning
confidence: 93%
“…Following offline inhibition of Interposed-VAL neurons, which aspect would be maintained and which would be lost? Faster relearning has been proposed to reflect an improved performance at selecting successful strategies (Morehead et al, 2015;Ruitenberg et al, 2018). An attractive possibility could be that novel sensory-motor correspondences encountered on the rotarod would remained learned, possibly leaving a memory trace within the cerebellum, but these elementary 'strategies' would not be properly temporally ordered into a sequence over the duration of a trial (2 minutes); the next day learning session would benefit from the existence of these fragments of skill, but learning would still be required to order them properly.…”
Section: Contribution Of Val-projecting Cerebellar Neurons To Offlinementioning
confidence: 99%